Organizational Commitment in Mediating the Work Environment and Compensation on Employee Performance - M Iksal Ilham; Yulianingsih; Palahudin (International Journal of Educational and Life Sciences, 2025)
This research aims to analyze the influence of organizational commitment in mediating the work environment and compensation on employee performance at PT. Japfa Comfeed Indo. Tbk Parungkuda Hatchery Unit. Data was collected through questionnaires from 92 employees and analyzed using the IBM SPSS v25 application with the path analysis method. The research results show that the work environment and compensation have an influence on employee performance, and organizational commitment is able to mediate the relationship between the work environment and compensation on employee performance. Based on these findings, it is recommended that companies improve work facilities, provide appropriate benefits, and strengthen normative commitments to increase employee satisfaction and productivity.